Biografi KH. Yusuf Muhammad dan Pemikiran Politiknya - Alfian Ghofur; Badrun Badrun (Local History & Heritage, 2022)
This article, entitled biography of KH. Yusuf Muhammad and his thoughts in politics, are NU figures who have a big role in national politics. This writing aims to find out the background of Gus Yus’ life as a boarding school caretaker and plunged into the world of politics. As for the writer took several formulations of the problem, namely (1) knowing the biography of KH. Yusuf Muhammad, (2) to find out his thoughts in the PKB Faction of the MPR-RI. Therefore, this article is a literature survey using historical research methods, namely heuristics, verification, interpretation, historiography.